The Mediating Role of Extreme Peer Orientation in the Relationships between Adolescent-Parent Relationship and Diabetes Management - Drew, Linda M. (2010)
The study examined whether the quality of the adolescent-parent relationship was associated with better diabetes management in adolescents with type 1 diabetes by decreasing adolescents' extreme peer orientation. Adolescents (n=252; 46% male and 54% female) aged 10-14 years with type 1 diabetes completed assessments of extreme peer orientation (i.e., tendency to ignore parental advice and diabetes care in order to fit in with friends), adolescent-parental relationship, and adherence; HbA1c scores indexed metabolic control. Adolescents with higher quality relationships with parents reported less peer orientation and better diabetes care. The mediational model revealed that adolescents' high quality relationships with their parents (mother and father) were associated with better treatment adherence and metabolic control through less peer orientation. It is likely that high quality adolescent-parent relationships may be beneficial to adolescent diabetes management through a healthy balance between peer and parental influence.